Penambahan Bahan Organik dan NAA terhadap Pertumbuhan Anggrek Hasil Persilangan Coelogyne secara In Vitro - Sri Hartati; Ahmad Yunus; Dwi Alma Indah Puji Astuti (Universitas Sebelas Maret, 2025)
Orchids are ornamental plants that have a high selling value so they are very prospective in the world of the ornamental plant business. This high economic value means that market demand for orchid commodities tends to increase. Efforts made to meet the need for orchids in the market are by propagating orchids using in vitro culture. This research aims to determine the effect of adding organic materials and NAA on the growth of orchids resulting from crossing Coelogyne pandurata and Coelogyne rumphii in vitro. This research used a completely randomized design (CRD) with two factors, namely the type of organic material (tomato, carrot and potato) and the concentration of ZPT NAA (0, 1 and 2 ppm). The research results showed that the addition of potato and tomato organic materials to the VW base medium was able to stimulate plant growth. The added NAA concentrations of 1 and 2 ppm are able to stimulate optimal plant growth. The combination of adding tomato organic matter and 1 ppm NAA concentration had the best growth in the number of roots and leaves, while adding tomato organic matter and 2 ppm NAA had the best growth in the number of shoots. The combination of adding potato organic material and 2 ppm NAA can stimulate plant height growth.